Innovative way to break the stone: Master lithoclast for bilateral simultaneous Percutaneous Nephrolithotomy - Waqar Ahmed; Adeel Mahesar; Javed Altaf Jat; Imran Idrees; Kashifuddin Qayoom; Pooran Mal; Tariq, Sana (Journal of the Pakistan Medical Association, 2022)
The objective of our study was to evaluate the efficacy of Master Lithoclast, also known as trilogy lithoclast, in simultaneous bilateral Percutaneous Nephrolithotomy (PCNL). The study was a prospective case series, involving 40 patients undergoing bilateral simultaneous PCNL, with 20 (50%) males and 20 (50%) females. The mean age of subjects was 32.9 ± 7.9 years. In Guy’s stone scoring 7(17.5%) patients classified in Group I, 28 (70%) in group II and the remaining 5(12.5%) patients were placed in group III. Total operative time observed was 74.8 ± 17.9 minutes. Complete stone clearance was observed in 30 (75%) patients. In conclusion, study data confirmed that Master Lithoclast provides faster stone clearance and is unaffected by the composition of stones, ease of usability, and improved tissue safety with reduced chances of fragments blocking are key factors. Keywords: Master lithoclast, Simultaneous bilateral PCNL, Trilogy lithoclast, Renal stone.